TET2- and TDG-mediated changes are required for the acquisition of distinct histone modifications in divergent terminal differentiation of myeloid cells. Issue 17 (29th September 2017) - Garcia-Gomez, Antonio; Li, Tianlu; Kerick, Martin; Català-Moll, Francesc; Comet, Natalia R.; Rodríguez-Ubreva, Javier; de la Rica, Lorenzo; Branco, Miguel R.; Martín, Javier; Ballestar, Esteban
Abstract: The plasticity of myeloid cells is illustrated by a diversity of functions including their role as effectors of innate immunity as macrophages (MACs) and bone remodelling as osteoclasts (OCs). TET2, a methylcytosine dioxygenase highly expressed in these cells and frequently mutated in myeloid leukemias, may be a key contributor to this plasticity. Through transcriptomic and epigenomic analyses, we investigated 5-methylcytosine (5mC), 5-hydroxymethylcytosine (5hmC) and gene expression changes in two divergent terminal myeloid differentiation processes, namely MAC and OC differentiation. MACs and OCs undergo highly similar 5hmC and 5mC changes, despite their wide differences in gene expression. Many TET2- and thymine-DNA glycosylase (TDG)-dependent 5mC and 5hmC changes directly activate the common terminal myeloid differentiation programme. However, the acquisition of differential features between MACs and OCs also depends on TET2/TDG. In fact, 5mC oxidation precedes differential histone modification changes between MACs and OCs. TET2 and TDG downregulation impairs the acquisition of such differential histone modification and expression patterns at MAC-/OC-specific genes. We prove that the histone H3K4 methyltransferase SETD1A is differentially recruited between MACs and OCs in a TET2-dependent manner. We demonstrate a novel role of these enzymes in the establishment of specific elements of identity and function in terminal myeloid differentiation.